Effect of Acid Hydrolysis and Thermal Hydrolysis on Solubility and Properties of Oil Palm Empty Fruit Bunch Fiber Cellulose Hydrogel - Sinyee Gan; Sarani Zakaria; Peivun Ng; Chin Hua Chia; Ruey Shan Chen (BioResources, 2015)
Cellulose hydrogel was produced from pretreated oil palm empty fruit bunch fiber (EFB) that went through acid hydrolysis and thermal hydrolysis. The pretreated EFB was dissolved in LiOH/urea aqueous solution using the rapid dissolution method and was subjected to a crosslinking process with the aid of epichlorohydrin to form hydrogel. The effects of both hydrolyses’ time on average molecular weight (Mŋ), solubility, and properties of EFB hydrogels were evaluated. Both hydrolyses led to lower Mŋ, lower crystallinity index (CrI) and hence, resulted in higher cellulose solubility. X-ray diffraction (XRD) characterization revealed the CrI and transition of crystalline structure of EFB from cellulose I to II. The effects of hydrolysis time on the transparency, degree of swelling (DS), and morphology of the regenerated cellulose hydrogel were also investigated using an ultraviolet-visible (UV-Vis) spectrophotometer and a Field emission scanning electron microscope (FESEM), respectively. These findings provide an efficient method to improve the solubility and properties of regenerated cellulose products.